An Uncommonly Difficult Business: Reviewing Women’s Writing in Eighteenth‑Century London’s Subscription Publishing, 1749–1774 - Byers, Clare (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2021)
In eighteenth-century London, publishing began to transition from a patronage system to a commercial business. An increase in literary reviews accompanied the shift. Publishing by subscription emerged as an evolving form of patronage where authors received monetary support from readers before publication. Women authors found subscription publishing welcoming as a means to avoid the commercial marketplace. Some authors used this publishing method in the name of seeking charitable support. Reviewers linked subscription publishing to female authors and acts of charity as reviewers attempted to circumvent the problem of potentially alienating their own readership, who could be subscribers. Through rhetorical analysis of 171 digitized bound volumes of 11 of London’s literary review periodicals, this paper argues that reviewers’ treatment of women authors and the associated use of subscription publications led to a disparaging perception of both by London’s growing reading public.